Real-World Oncological Outcomes of Nivolumab Plus Ipilimumab in Advanced or Metastatic Renal Cell Carcinoma: A Multicenter, Retrospective Cohort Study in Japan - Tomoki Taniguchi; Koji Iinuma; Kei Kawada; Takashi Ishida; Kimiaki Takagi; Masayuki Tomioka; Makoto Kawase; Kota Kawase; Keita Nakane; Yuki Tobisawa; Takuya Koie (Current Oncology)
A combination of nivolumab and ipilimumab (NIVO + IPI) is the only approved combination of two immune checkpoint inhibitors for metastatic or advanced renal cell carcinoma (mRCC). Inadequate evidence of treatment with NIVO + IPI has been reported in Japanese cohorts. We evaluated the clinical efficacy of NIVO + IPI treatment. Patients with mRCC who received NIVO + IPI at nine Japanese facilities between August 2018 and March 2023 were enrolled in this study. The primary endpoint in this study was the assessment of oncological outcomes in patients with mRCC who received NIVO + IPI. Eighty-four patients with mRCC were enrolled. The median follow-up period was 18.3 months, and median progression-free and overall survival were 13.3 and 50.9 months, respectively. The objective response rate was 47.6%, and the disease control rate was 78.6%. To our knowledge, this is the largest study that evaluates Japanese patients with mRCC receiving NIVO + IPI treatment. In this study, the real-world oncological outcomes after NIVO + IPI treatment were comparable to those in the CheckMate 214 study.